Parental use of routines, setting limits, and child screen use during COVID-19: findings from a large Canadian cohort study - Lien, Amanda; Li, Xuedi; Keown-Stoneman, Charles D. G.; Cost, Katherine T.; Vanderloo, Leigh M.; Carsley, Sarah; Maguire, Jonathon; Birken, Catherine S. (Frontiers in Child and Adolescent Psychiatry, 2024)
Background An increase in child screen time has been observed throughout the COVID-19 pandemic. Home environment and parenting practices have been associated with child screen time. The purpose of this study was to examine associations between parental use of routines, limit setting, and child screen time during the (COVID-19) pandemic to inform harm-reducing strategies to limit the potential harms ensued by excessive screen use. Methods A cohort study was conducted in 700 healthy children (3,628 observations) aged 0–11 years though the TARGet Kids! COVID-19 Study of Children and Families in Toronto, Canada from May 2020-May 2021. The independent variables assessed were parent-reported use of routines and setting limits. Outcomes were parent-reported child daily screen time in minutes and whether the Canadian 24-Hour screen time guideline was met, defined as 0 for <1 years, 60 or less for 1–5 years, and 120 or less for >5 years. Linear and logistic mixed-effects models were fitted using repeated measures of independent variables and outcomes with a priori stratification by developmental stages (<3, 3–4.99, ≥5 years). Results A total of 700 children with 3,628 observations were included in this study [mean age = 5.5 (SD = 2.7, max = 11.9) years, female = 47.6%]. Mean change in child screen time before vs. during the pandemic was +51.1 min/day and level of parental use of routines and setting limits remained stable. Lower use of routines was associated with higher child screen time (β = 4.0 min; 95% CI: 0.9, 7.1; p = 0.01) in ages ≥5 years and lower odds of meeting the screen time guideline in ages <3 years and ≥5 years (OR = 0.59; 95% CI: 0.38, 0.88; p = 0.01; OR = 0.76; 95% CI: 0.67, 0.87; p < 0.01). Lower use of limit setting was associated with higher child screen time and lower odds of meeting the screen time guideline in ages ≥5 years (β = 3.8 min; 95% CI: 0.69, 6.48; p < 0.01; OR = 0.86; 95% CI: 0.78, 0.94; p < 0.01). Conclusions Lower parental use of routines and limits during the COVID-19 pandemic were associated with higher screen time and lower odds of meeting the screen time guideline among school-age children. Results may help inform strategies to promote healthy screen use in this age group.